Spatially modulated and supersymmetric mass deformations of N=4 SYM - Arav,I; Cheung,KCM; Gauntlett,JP; Roberts,MM; Rosen,C (arXiv, 2020)
We study mass deformations of $\mathcal{N}=4$, $d=4$ SYM theory that arespatially modulated in one spatial dimension and preserve some residualsupersymmetry. We focus on generalisations of $\mathcal{N}=1^$ theories andshow that it is also possible, for suitably chosen supersymmetric masses, topreserve $d=3$ conformal symmetry associated with a co-dimension one interface.Holographic solutions can be constructed using $D=5$ theories of gravity thatarise from consistent truncations of $SO(6)$ gauged supergravity and hence typeIIB supergravity. For the mass deformations that preserve $d=3$ superconformalsymmetry we construct a rich set of Janus solutions of $\mathcal{N}=4$ SYMtheory which have the same coupling constant on either side of the interface.Limiting classes of these solutions give rise to RG interface solutions with$\mathcal{N}=4$ SYM on one side of the interface and the Leigh-Strassler (LS)SCFT on the other, and also to a Janus solution for the LS theory. Anotherlimiting solution is a new supersymmetric $AdS_4× S^1× S^5$ solutionof type IIB supergravity.